Perceptions of sexist language and its relationship to attitudes toward women and social roles : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Scott, Rachel Ann (Massey University, 1993)
The language about women reflects the attitudes of men toward women and to the extent that women use them, the attitudes of women toward themselves. The relationship between language and the attitudes of those who use it is not one-way. Language reflects the attitudes of those who use it but it can also create and maintain attitudes and stereotypes. Hence the feminists' attack on the English language. The trend to using non-sexist language is a conscious effort to change our thought by changing our language. The present study investigated the existence of a relationship between attitudes toward women, social attitudes, and people's perceptions of sexist language for 151 participants. The sample included two student groups (internally enroled students and extramural students) and a non-student sample. The sample completed self-report questionnaires on their judgements of language as sexist, their perceptions of sexist language as a problem, and attitudes toward women and social issues. The findings demonstrated that there is a relationship between sexist language and the attitudes people espouse. Liberal social attitudes and liberal attitudes toward women and gender roles were found to correlate with easier recognition of linguistic sexism. Traditional attitudes toward gender roles and conservative social attitudes resulted in a failure to perceive gender-biased language as sexist.
Keywords: Sexism in language; English language -- Sex differences; English language -- Usage; Sexism